The use of negative pressure wound therapy to prevent post-operative surgical site infections following pancreaticoduodenectomy. Issue 9 (September 2017) - Burkhart, Richard A.; Javed, Ammar A.; Ronnekleiv-Kelly, Sean; Wright, Michael J.; Poruk, Katherine E.; Eckhauser, Frederic; Makary, Martin A.; Cameron, John L.; Wolfgang, Christopher L.; He, Jin; Weiss, Matthew J.
Abstract: Background: Rates of superficial surgical site infection (SSI) following pancreaticoduodenectomy remain high. Following resection for cancer, complications such as SSI impact adjuvant therapy delivery and portend worse survival. An incisional negative pressure dressing (iVAC) has been demonstrated to reduce SSI in other high-risk cohorts. Methods: Following a comprehensive effort to identify patients at high risk for SSI, the practice patterns at a single academic center shifted and iVAC use increased. SSI rates were tracked in a prospectively maintained database and are reported. Results: 394 patients underwent pancreaticoduodenectomy over 21 months. 120 patients (30.5%) had an iVAC applied. The overall rate of SSI was 19.8%. On multivariate analysis, increased risk for SSI was associated with neoadjuvant therapy, preoperative biliary interventions and prior abdominal surgery. iVAC use decreased the rate of SSI (OR 0.45, p = 0.015). In the highest-risk patients, SSI rate declined from 50% in patients without an iVAC to 19.1% with iVAC use (p = 0.015). Conclusion: The use of an iVAC following pancreaticoduodenectomy is associated with decreased SSI rates. This is particularly true for patients at highest risk as defined by a previously established risk scoring system in patients undergoing open pancreaticoduodenectomy.